Research data management : a European perspective - Kruse, Filip; Thestrup, Jesper Boserup (Current topics in library and information practice., 2018)
Based on case studies this book offers an insight in various European activities and practices in data management and their interaction with policies and programs. The latter form the background for the following case studies, provide the conceptual framework, at the same time giving an exhaustive understanding of the specific subjects. The case studies share common themes and give a concrete insight into vital issues such as web archiving, digitization of analog archives, researchers' motivations for sharing data, and how libraries, archives and researchers can collaborate in creating research tools and services.